Where are my shoes? - Bodman, Sue; Franklin , Glen (Cambridge : Cambridge University Press, 2017)
Taj can't find his shoes. Where are they? A character searches everywhere for their missing shoes, asking others for help, and finally finds them in a funny or unexpected place.
Keywords: English - book